The Influence Of Work Motivation And Job Satisfaction On Employee Performance Through Employee Engagement - Antonius; Lista Meria (International Journal of Economics (IJEC), 2025)
This study aims to examine how direct and indirect influence of work motivation, job satisfaction and employee continuity on employee performance atPT. Gajah Tunggal Tbk. This study was motivated by employee performance that was not mentioned so that a study was conducted to determine work motivation, job satisfaction and employee continuity which would later become the most influential variables on employee performance at PT. Gajah Tunggal Tbk. The population in this study were permanent employees at PT. Gajah Tunggal Tbk. and had worked for more than 1 year. While the research sample was taken using purposive sampling technique with a total of 200 respondents. This study is a quantitative study using the Structural Equation Model - Partial Least Square (SEM-PLS) method. The results of the study showed that work motivation was proven to have a positive effect on employee performance, job satisfaction had a positive effect on employee performance, work motivation had a positive effect on employee performance, job satisfaction did not have a positive effect on employee performance, the closest employee had a positive effect on employee performance and an indirect effect that was proven that employee turnover was able to mediate work motivation and job satisfaction on employee performance. After conducting the study, the researcher suggested expanding the population to the branches of PT. Gajah Tunggal Tbk located in other regions in Indonesia, in order to represent more answers from PT. Gajah Tunggal Tbk employees throughout Indonesia. In addition, it can also add other supporting variables, such as training, work environment, compensation, reward and punishment and other variables that are relevant to the novelty of the study